DAMPAK TOXIC FRIENDSHIP PADA MAHASISWA UNIVERSITAS BHAYANGKARA JAKARTA RAYA DAN STRATEGI ANTISIPASI DALAM MENCIPTAKAN LINGKUNGAN PERTEMANAN YANG SEHAT - Jesyinda Putri Wibowo; Zefanya Muri Putri Kristyanti, Talitha Fairuz Marsya Nugraha, Adelia Ananda Putri, Putri Fauziyyah (CV. ADIBA ASIHA AMIRA, 2025)
The phenomenon of toxic friendship among Bhayangkara University of Greater Jakarta students, which has a negative impact on mental, social, and academic health. Using a qualitative phenomenological approach, this study involved a psychoeducational intervention consisting of a pre-test, material delivery, and post-test to measure the effectiveness of the program. The psychoeducation included an understanding of the characteristics, impacts, and anticipation strategies of toxic friendship, emphasizing Ibn Miskawaih's principles of friendship ethics, such as choosing friends wisely, maintaining healthy boundaries, and prioritizing cooperation. The results showed an increase in students' understanding of toxic friendship and the importance of building healthy friendships. This study contributes to the toxic friendship literature and offers practical solutions through psychoeducation and the formation of support groups to create a positive friendship environment on campus.